The Ultrastructure of the Adrenal Zona Glomerulosa of Rats on Potassium-Supplemented or Sodium-Depleted Diets - Domoto, Douglass T. (1973)
Ultrastructural changes in the mitochondria and other organelles in zona glomerulosa cells of the adrenal cortex were noted in rats maintained for up to 8 days on a potassium-enriched or a sodium-deficient diet. In both groups of animals, aldosterone production is known to be increased. Principal ultrastructural changes in the rats maintained on a potassium-supplemented or a sodium-deficient diet consisted of a loss of electron density of the mitochondrial matrix and a change from plate-like cristae to tubular-vesicular cristae. These changes were similar in both potassium-enriched and sodium-depleted animals after 8 days and were markedly different from control animals. Morphologic changes occurred after the initial increase in aldosterone production, which has been measured in 1 to 2 days in both sodium-depleted and potassium-enriched rats. The mitochondrial changes described are probably related to the persistent increased active steroid synthesis.